Analisis Kesehatan Bank Menggunakan Metode RGEC pada Bank Syariah dan Bank Konvensional Tahun 2018-2020 - Ipur Nindiani; Titi Rapini; Riawan Riawan (Edumedia Solution, 2023)
A corporation in absolute banking must have a level of public trust. Assessing the soundness of a bank is one of the techniques to keep the relationship strong. This study examines the soundness level of Islamic banks and conventional banks using the RGEC method in accordance with Bank Indonesia Regulation No. 13/1/PBI/2011. This study uses descriptive quantitative methods from the financial statements of each bank. The research results on the Risk Profile aspect measured by the ratio of NPL and LDR for each of three years are included in the very healthy category. In the aspect of Good Corporate Governance (GCG), it is included in predicate 2 with the healthy category. Then the overall earning aspect for three years is included in the very healthy category. Finally, the Capital ratio for three years of each bank is in a very healthy condition